Pengembangan Media Pembelajaran Model STEM pada Konsep Terapung Melayang Tenggelam untuk Memfasilitasi Keterampilan Saintifik Anak Usia Dini - Santika, Desi Arianti; Mulyana, Edi Hendri; Nur, Lutfi (Universitas Pendidikan Indonesia (UPI), 2020)
This research is motivated by problems that occur in the field related to the use of STEM learning media in the concept of floating, floating and sinking which are limited and even lack of learning media facilities. The learning process in PAUD will be carried out optimally if it gets the support of relevant components and is very important in the delivery of information on the concept of learning materials in this case the learning media. STEM is an interdisciplinary merger of science related to science, technology, engineering and mathematics. STEM learning media model